Mediating role of binding moral foundations between dogmatism, social dominance orientation and perceived threat from Syrian asylum seekers in Turkey - Bozkus-Demir, Olcay; Akgun, Serap (Springer, 2024)
Can attitudes toward social groups be considered in the context of morality? To that purpose, two studies assessed whether dogmatism, social dominance orientation, and moral foundations predict perceived threats from Syrian asylum seekers in Turkey. In the first study, Structural Equation Modeling analyses revealed that dogmatism and social dominance orientation predicted the perception of threat via the mediating role of binding moral foundations, whereas individualizing moral foundations did not (N = 235). The second study collected data from a larger sample (N = 438) and used Moral Foundations Scenarios to assess moral concerns, replicating the first study's findings. Furthermore, it was shown that an alternative model in which individualizing and binding moral foundations predicted threat via dogmatism and SDO mediating did not fit the data. The findings are discussed in light of the possibility that moral judgments are a product of motivated social cognition.
Keywords: Social dominance orientation; Dogmatism; Moral foundations; Intergroup threat perception; Immigration